Professional Development of a Teacher in the ICT Era - Kusumaningrum, A; ., Suharno; ., Triyanto (KnE Social Sciences, 2019)
Teacher plays a significant role in educating. As an agent of change, the teacher should be perceptive to any change as the result of the modernism. It requires the teacher to possess more complex competence and idea. Therefore, competence development activities are needed for the teacher. The competence and professional development of teacher are expected to be able in improving the professional teacher quality and further improve the education quality. This research was aimed to describe the development of teacher profession in this ICT era. The method used was a literature study. The data from the research showed that 1) The professional development can be done through the activities within the working area, and 2) There are some factors affecting the teacher’s professional development. Teacher plays a significant role in educating. As an agent of change, the teacher should be perceptive to any change as the result of the modernism. It requires the teacher to possess more complex competence and idea. Therefore, competence development activities are needed for the teacher. The competence and professional development of teacher are expected to be able in improving the professional teacher quality and further improve the education quality. This research was aimed to describe the development of teacher profession in this ICT era. The method used was a literature study. The data from the research showed that 1) The professional development can be done through the activities within the working area, and 2) There are some factors affecting the teacher’s professional development. Keywords: development, ICT era, professionalism, teacher. Keywords: development, ICT era, professionalism, teacher